Measurement of time-dependent CP-violating asymmetries in B-0 -> K-*0 gamma(K-*0 -> K-S(0)pi(0)) decays - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Tisserand, V; Zghiche, A; Palano, A; Pompili, A; et al. (2004)
A measurement of the time-dependent CP-violating (CPV) asymmetries in a b → sy process through the exclusive decay, was performed. A systematic uncertainty of 0.02 (0.02) due to tagging asymmetries in the signal and 0.02 (0.02) due to imperfect knowledge of the probability distribution function (PDF) was included. An event-shape Fisher discriminant in the maximum-likelihood fit was employed, from which the CPV measurements were extracted. For the continuum background, the functional form of the PDF was selected, which described each fit variable in data using the sideband regions of the other observables.